Assessing the quality of tuberculosis evaluation for children with prolonged cough presenting to routine community health care settings in rural Uganda. - Carina Marquez; J Lucian Davis; Achilles Katamba; Priscilla Haguma; Emmanuel Ochom; Irene Ayakaka; Gabriel Chamie; Grant Dorsey; Moses R Kamya; Edwin Charlebois; Diane V Havlir; Adithya Cattamanchi (PLoS ONE)
Background Improving childhood tuberculosis (TB) evaluation and care is a global priority, but data on performance at community health centers in TB endemic regions are sparse. Objective To describe the current practices and quality of TB evaluation for children with cough ≥2 weeks' duration presenting to community health centers in Uganda. Methods Cross-sectional analysis of children (<15 years) receiving care at five Level IV community health centers in rural Uganda for any reason between 2009-2012. Quality of TB care was assessed using indicators derived from the International Standards of Tuberculosis Care (ISTC). Results From 2009-2012, 1713 of 187,601 (0.9%, 95% CI: 0.4-1.4%) children presenting to community health centers had cough ≥ 2 weeks' duration. Of those children, only 299 (17.5%, 95% CI: 15.7-19.3%) were referred for sputum microscopy, but 251 (84%, 95% CI: 79.8-88.1%) completed sputum examination if referred. The yield of sputum microscopy was only 3.6% (95% CI: 1.3-5.9%), and only 55.6% (95% CI: 21.2-86.3%) of children with acid-fast bacilli positive sputum were started on treatment. Children under age 5 were less likely to be referred for sputum examination and to receive care in accordance with ISTC. The proportion of children evaluated in accordance with ISTC increased over time (4.6% in 2009 to 27.9% in 2012, p = 0.03), though this did not result in increased case-detection. Conclusion The quality of TB evaluation was poor for children with cough ≥2 weeks' duration presenting for health care. Referrals for sputum smear microscopy and linkage to TB treatment were key gaps in the TB evaluation process, especially for children under the age of five.